Comparative impact of tertiary lymphoid structures and tumor-infiltrating lymphocytes in cholangiocarcinoma - Chun-Nan Yeh; Yu-Chan Chang; Yi-Chen Yeh; Yu-Chao Wang; Dennis Shin-Shian Hsu; Meng-Lun Lu; Michael Hsiao; Ming-Huang Chen; Nai-Jung Chiang; Shin-Yi Chung; Chien-Jung Huang; Ming-Hsien Chan; et al. (Journal for ImmunoTherapy of Cancer)
Background Cholangiocarcinoma is a challenging malignancy with limited responses to conventional therapies, particularly immune checkpoint inhibitor therapy. Tumor-infiltrating lymphocytes (TILs) and tertiary lymphoid structures (TLSs) are key components of the tumor microenvironment (TME) and have been implicated in the immune response to cancer. However, the role and difference of TLSs and TILs in patients with cholangiocarcinoma remains unclear. This study elucidates their contributions to the TME.Methods We examined 16 tumor samples from a single-arm, phase II trial of nivolumab plus modified gemcitabine and S-1 and various datasets. Immunohistochemistry and RNA sequencing were employed to assess TLSs and TILs presence and activity. Differential gene expression and signature of immune cell composition were examined by GeoMx Digital Spatial Profiler and Cancer Transcriptome Altas analysis.Results TLS-positive (N=7) patients demonstrated significantly better immunotherapy outcomes compared with TLS-negative (N=9) patients, including higher objective response rates (71% vs 0%) and disease control rates (100% vs 67%). The presence of TLSs correlated with improved progression-free and overall survival (p=0.03). TLSs were associated with “inflamed” tumors characterized by substantial immune infiltration, particularly involving T and B cells. Gene expression analyses identified significant upregulation of B cell-related genes in TLSs. Additionally, TLSs exhibited higher properties of memory B cells and myeloid dendritic cells but lower levels of innate immune cells compared with TILs. T cells within TLSs showed elevated expression of precursor-exhausted-related genes and lower cytotoxicity signature. Furthermore, TILs in TLS-positive tumors had higher levels of exhaustion signatures compared with TILs in TLS-negative tumors. Clinical data corroborated these findings, with higher PD-L1 and LAG-3 expression in TLS-positive tumors.Conclusion Our findings revealed that TILs in TLS-positive tumors have more exhausted T cell signature and PD-1 and LAG-3 protein expression in CCA which support our clinical finding. TLSs can predict favorable immunotherapy responses in patients with cholangiocarcinoma, highlighting their potential as a biomarker and therapeutic target to enhance treatment efficacy.